Capitalization and Punctuation Used in Writing Narrative Text - Nur’ainy, Siti Asma; Johan, Andrian Nuriza; Masykuri, Edi Sunjayanto; Dewi, Puspa; Tusino, Tusino (Scripta : English Department Journal, 2023)
The aims of this study are to describe how capitalization and punctuation are used by students of the tenth grade level in writing narrative text and to find out the students’ difficulties in using capitalization and punctuation at SMA Negeri 4 Purworejo. This study used descriptive qualitative method. The researcher used a writing test and a questionnaire to collect data. The data was collected in SMA Negeri 4 Purworejo on April 8 and 11, 2022. The researcher used 102 students as study subjects. The results of the test showed that most of the students mastered the use of capitalization more than punctuation. The researcher found that there were 3314 correct answers for capitalization (58%) and 2572 correct answers of punctuation (41%). Meanwhile, the results of the questionnaire revealed that the students struggled with capitalization and punctuation. In capitalization, there were 62 students who did not understand the rules of capitalization correctly (61%). In punctuation, there were 50 students who had difficulty in using periods (49%), 62 students who had difficulty in using commas (61%), 57 students who had difficulty in using question marks (56%), 56 students who had difficulty in using apostrophes (55%), and 68 students who had difficulty in using exclamation points (67%). Most of the students had difficulties in punctuation used, especially in exclamation points. The researcher suggests that the teacher give his or her students more practice in order to enhance their writing ability, particularly in the correct use of capitalization and punctuation.